Youngiasides A and C Isolated from Youngia denticulatum Inhibit UVB-Induced MMP Expression and Promote Type I Procollagen Production via Repression of MAPK/AP-1/NF-kappa B and Activation of AMPK/Nrf2 in HaCaT Cells and Human Dermal Fibroblasts - Kim, Myungsuk; Park, Young Gyun; Lee, Hee-Ju; Lim, Sue Ji; Nho, Chu Won (AMER CHEMICAL SOC, 2015)
This study investigated the effects of youngiaside A (YA), youngiaside C (YC), and Youngia denticulatum extract (YDE) on extrinsic aging and assessed its molecular mechanisms in UVB-irradiated HaCaT keratinocytes and human dermal fibroblasts (HDFs). The results showed that YA, YC, and YDE decreased matrix metalloproteinase (MMP) expression and production in HaCaT cell and HDFs and increased collagen expression and production in HDFs. In addition, YA, YC, and YDE significantly increased antioxidant enzyme expression, thereby down-regulating UVB-induced reactive oxygen species (ROS) production and ROS-induced mitogen-activated protein kinase (MAPK) and activator protein-1 (AP-1) signaling in HaCaT cells. Furthermore, YA, YC, and YDE reduced phosphorylation of I?Ba and IKK alpha/beta, blocked nuclear factor-kappa B (NF-kappa B) p65 nuclear translocation, and strongly suppressed pro-inflammatory mediators. Finally, YA, YC, and YDE augmented UVB-induced adenosine monophosphate activated protein kinase (AMPK) phosphorylation and YA and YC did not inhibit MMP-1 production in AMPK inhibitor or nuclear factor-erythroid 2-related factor-2 (Nrf2) siRNA-treated HaCaT cells. The results suggest that these compounds could be potential therapeutic agents for prevention and treatment of skin photoaging.
Keywords: MATRIX METALLOPROTEINASES; OXIDATIVE DAMAGE; KAPPA-B; ULTRAVIOLET; MECHANISMS; PROTECTS; GENE; INDUCTION; EXPOSURE; EXTRACT